(untitled) (New York, 2000)
text provides 19 in-depth, critical reviews on specific chemical and physical agents or classes of agents that either have major impacts on the health of the general public or at least a strong likelihood of such effects. The introductory chapter and the three closing chapters deal with generic issues and concerns, and place the critical review chapters in a larger perspective. For public health officials, industrial safety managers and hygienists, epidemiologists, and primary health care professionals who make decisions on risk assessment and risk management for individuals and populations
Keywords: Environmental health,Environmental toxicology,Sức khỏe môi trường,Độc chất học môi trường